Cường độ tìm kiếm trên Google và thị trường chứng khoán Việt Nam: Sự chú ý hay sự không chắc chắn? - Nguyen Thu, Hoai (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study examines whether the Google search volume reflects investor attention or uncertainty in the Vietnamese stock market by testing two competing hypotheses within a unified framework. Using weekly panel data from 88 HOSE-listed stocks over the period from 2019–2023, we apply the Fama-French five-factor model with lagged variables to capture short-term behavioral responses. The findings indicate that search volume positively affects stock returns in the current week but has a negative effect one week later, supporting the investor attention hypothesis. Robustness is confirmed through subsample analyses by firm size and post-COVID-19 interaction. The results suggest that Google search volume primarily reflects attention-driven behavior rather than uncertainty, and may serve as a behavioral indicator for market monitoring in frontier markets.
Keywords: Investor uncertainty; Investor attention; Stock return; Search volume